Evaluation of the Potential Therapeutic Properties of Liquidambar orientalis Oil - Cengiz Baloglu, Mehmet; Yildiz Ozer, Lutfiye; Pirci, Buket; Zengin, Gokhan; Ibrahim Uba, Abdullahi; Celik Altunoglu, Yasemin (Wiley, 2023)
AbstractLiquidambar orientalis Mill., commonly called the Anatolian sweetgum or Sigla tree, is endemic to southwestern Turkey. It has been historically significant in traditional medicine. In our research, we delved into the therapeutic attributes of its oil, emphasizing its antioxidant, antimicrobial, and antitumor properties. The primary chemical constituent of the gum is styrene, accounting for 78.5 %. The gum demonstrated antioxidant capabilities in several assays, including in 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH), 2,2′‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS), cupric reducing antioxidant capacity (CUPRAC) and ferric reducing antioxidant power (FRAP). It displayed bactericidal actions against various gram‐positive bacteria, such as Staphylococcus aureus, and gram‐negative strains, including Escherichia coli. Additionally, the oil showcased potent antitumor effects against breast (MDA‐MB‐231), lung (A549), and prostate (PC3) cancer cell lines. These effects were found to be both time‐ and dose‐dependent. L. orientalis Mill. oil showed the best antitumor activity against breast, lung, and prostate cancer cell lines after the 24 h and 48 h treatment. Its oil might induce autophagy in the PC3 prostate cancer cell line, whereas its cytotoxicity against MDA‐MB‐231 and A549 cancer cell lines might not be correlated with autophagy or apoptosis pathways. In conclusion, the oil from the Sigla tree offers promising therapeutic potential and warrants further exploration.
Keywords: chemical and antioxidant profiles; sweetgum tree; biological activity oil; molecular docking; antitumor agents; 3. Good health